Knowledge and behavior regarding breast cancer screening among female teachers in Selangor, Malaysia. - Parsa, Parisa; Kandiah, Mirnalini; Mohd Zulkefli, Nor Afiah; Abdul Rahman, Hejar (Asian Pacific Organization for Cancer Prevention, 2008)
A cross-sectional study was carried out to determine the knowledge and practices of 425 female secondary school teachers from 20 selected secondary schools in Selangor, Malaysia on breast cancer screening (BCS). A self-administered, structured questionnaire was used for data collection. This study showed moderate to low knowledge on breast cancer (BC) and BCS among teachers. Only 19%, 25% and 13.6% eligible women performed breast self-examination (BSE), clinical breast examination (CBE) and mammography respectively, on a regular basis. Level of breast cancer knowledge was significantly associated with BSE (p=0.000). Having heard/ read about BCS, and regular visit with a physician were associated with BCS behaviors (P<0.05). There was no association between BCS behaviors (P>0.05 and age, family history of breast cancer, marital status or having health insurance). Efforts are needed to increase knowledge and remove misconceptions about breast cancer and screening practices among Malaysian women.